2009
DOI: 10.1007/s11095-009-0011-3
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Vaccines: Recent Progress in Understanding the Natural Barriers

Abstract: It has long been known that protection against pathogens invading the organism via mucosal surfaces correlates better with the presence of specific antibodies in local secretions than with serum antibodies. The most effective way to induce mucosal immunity is to administer antigens directly to the mucosal surface. The development of vaccines for mucosal application requires antigen delivery systems and immunopotentiators that efficiently facilitate the presentation of the antigen to the mucosal immune system. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 125 publications
0
51
0
Order By: Relevance
“…Mucosal applications of dental caries vaccines are generally preferred for the induction of sIgA antibody in the salivary compartment, since mucosal IgA immune responses are most efficiently induced by the administration of vaccines onto mucosal surfaces while injected vaccines are generally poor inducers of mucosal immunity [49]. Many investigators have shown that exposure of antigen to mucosally associated lymphoid tissue in the gut, nasal, bronchial, or rectal site can give rise to immune responses not only in the region of induction, but also in remote locations.…”
Section: Induction Of Specific Anti-caries Salivary Siga Antibodiesmentioning
confidence: 99%
“…Mucosal applications of dental caries vaccines are generally preferred for the induction of sIgA antibody in the salivary compartment, since mucosal IgA immune responses are most efficiently induced by the administration of vaccines onto mucosal surfaces while injected vaccines are generally poor inducers of mucosal immunity [49]. Many investigators have shown that exposure of antigen to mucosally associated lymphoid tissue in the gut, nasal, bronchial, or rectal site can give rise to immune responses not only in the region of induction, but also in remote locations.…”
Section: Induction Of Specific Anti-caries Salivary Siga Antibodiesmentioning
confidence: 99%
“…24,25 IgA has several functions in mucosal defense including the entrapment of antigens or pathogens in mucus to prevent them from direct contact with the mucosal surface. 15,26 In addition, sIgA may also block or provide steric hindrance to surfaces of pathogenic molecules that may inhibit their attachment to the epithelium. 27 The predominance of IgA in mucosal areas is a result of mutual collaboration between plasma cells and epithelial cells.…”
Section: Respiratory Epithelial Cellsmentioning
confidence: 99%
“…Those that have the ability to adhere to mucosal surfaces and selectively target M cells or APCs, should be the most effective. 18,26 Chitosan has been much investigated, and is a polysaccharide manufactured from chitin found in crustacean shells or fungi by a deacetylation process. Because of the range of sources this polymer is available in a range of molecular weights, but all are made up of repeating units of glucosamine and N-acetylglucosamine and bear a positive charge making it mucoadhesive.…”
Section: Formulation Approachesmentioning
confidence: 99%
See 2 more Smart Citations